Natural dynamics of hypertriglyceridemia: incidence, regression, mortality from cardiovascular diseases and all causes (according to the results of a 17-years prospective study) - I. V. Dolgalyov; I. V. Tsimbalyuk; V. V. Obraztsov; V. A. Seryakova; T. Yu. Konko; B. A. Trotsenko; R. S. Karpov (Бюллетень сибирской медицины, 2011)
In 17-year nested prospective study, the natural dynamics of hypertriglyceridemia (HTG) (development of new cases, regress), cardiovascular mortality and other mortality of patients with HTG have been examined. The nest included 630 men and 916 women from 20 to 59 years old. The HTG incident in the nest was 8.24 cases per 1000 people*years of observation. Among people 20—29 years old, new HTG cases were observed more often in men, while in the age interval of 30—59 years, new cases were more often observed in women. For the period of observation, the HTG occurrence increased 1.6 times in men and 2.1 times in women. HTG is characterized by the low course stability, and the regress level is independent of sex. Among men and women, Among men and women with HTG, brain stroke and cardiovascular mortality is higher than that among people with the normal triglyceride (TG) level. The TG level did not affect the total men mortality.